Social Responsibility of Public Institutions - Lazorenko, L. V.; Vorobiov, S. V. (Statistics of Ukraine, 2023)
The article discloses the essence of social responsibility of public institutions, defines the basic principles and models of social responsibility, highlights the components of social responsibility of public institutions, including: responsibility in lawmaking; responsibility in providing jobs for the population; responsibility in the field of social development; responsibility in the field of political activity; responsibility in international activities. The content of social responsibility of public institutions is defined, which includes: definition of a clear role and place of a public institution in the structure of the state and society, its social significance; coordination of the activities of public institutions with the task of implementing the functions of the state and local government; understanding of the need to act in full accordance with the interests of the state and society and accepted social requirements and norms; take into account various factors of influence of the external environment on the activities of public institutions in order to ensure their social significance; striving for maximum subordination, a responsible approach to their activities. The social responsibility of public institutions has a significant impact on the level of corruption, human development and the fulfillment of international obligations. The effectiveness of public institutions, including in the aspect of implementing social programs, directly proportionally depends on the availability of a strategy that ensures the development of an approach to planning and implementation of appropriate measures that form their reputation. To increase the importance and importance of social responsibility public institutions need to develop a strategy for the development of social responsibility and the procedure for its implementation, which is based on a combination of certain levels, measures, directions and tools aimed at the development of social responsibility, the basis of which is the social orientation of public institutions. To implement the strategy of social responsibility of public institutions, it is expedient to use the mechanism of integrated management of social responsibility of public institutions, which is a system of interrelated management functions: planning, organization, motivation and control.